2012
DOI: 10.1590/s0044-59672012000300003
|View full text |Cite
|
Sign up to set email alerts
|

Estruturas secretoras em cipó-d'alho (Mansoa standleyi (Steyerm.) A. H. Gentry, Bignoniaceae): ocorrência e morfologia

Abstract: ResumoEspécies de Mansoa são denominadas de "cipó-d'alho", por exalarem odor de alho das partes vegetativas e reprodutivas. Contudo, dados sobre morfologia e distribuição das estruturas secretoras presentes em Mansoa são escassos e ausentes para M. standleyi. O presente trabalho objetivou caracterizar a ocorrência e morfologia das estruturas secretoras do eixo vegetativo aéreo de M. standleyi. Para tanto, amostras da lâmina foliolar e de regiões nodais foram fixadas e submetidas às técnicas histológicas e de m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
3
0
1
Order By: Relevance
“…Due to the diversity of glandular trichomes in the tribe, our analyses confirm the reports of several authors that evidenced the taxonomic value of these structures (Bureau and Schumann 1897;Seibert 1948;Gentry 1980;Vilhena-Potiguara et al 2012;Nogueira et al 2013;Gama et al 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Due to the diversity of glandular trichomes in the tribe, our analyses confirm the reports of several authors that evidenced the taxonomic value of these structures (Bureau and Schumann 1897;Seibert 1948;Gentry 1980;Vilhena-Potiguara et al 2012;Nogueira et al 2013;Gama et al 2013).…”
Section: Discussionsupporting
confidence: 90%
“…The terpenes were previously reported by Sousa et al [51] from extracts of the leaves and branches of M. hirsuta. Vilhema-Potiguara et al [52], analyzed Mansoa standleyi extracts and reported the metabolites class triterpenoids, flavonoids, naphthoquinones, and amino acids. Silva [53] identified the pentacyclic triterpenes ursolic acid and oleanolic acid from the ethyl acetate fraction of M. hirsuta leaves.…”
Section: H-nmrmentioning
confidence: 99%
“…These ants hunt both large and small prey such as grasshoppers, termites and wasps (Richard et al 2001), which could play a role in combatting on plant-preying insects. The presence of a secretory structure that release exudate as reward to insects allows for the mutualistic relationship between plants and insects, especially ants (Vilhena-Potiguara et al 2012).…”
Section: Amazonicamentioning
confidence: 99%